Low-Latency Searches for Gravitational Waves using the GstLAL Data Analysis Pipeline - Baylor, Amanda Christine (Proceedings of the Wisconsin Space Conference, 2023)
Compact binary mergers involving at least one neutron star could produce electromagnetic counterparts. Prompt alerts of the detection of gravitational waves (GWs) from these mergers allow for rapid follow-up on the sources and the potential detection of new physics surrounding their astrophysical processes. The GstLAL pipeline searches for and analyzes GW signals in low-latency, producing results in near real time. For more efficient EM follow-up, we focus on the development of early warning (EW) detections, which are alerts sent out prior to merger. We perform tests of an EW GstLAL pipeline using simulated signals in preparation for the LIGO-Virgo-KAGRA collaboration’s fourth observing run (O4). We also discuss the prospects for sending out an EW alert and localizing the signal with a four detector network.